Analysis of user satisfaction and the importance of services provided by privately owned gyms - Reyes Robles, Marina; Sánchez Félix, Daniel Armando; Ramírez Siqueiros, María Grethel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aims of this study were to determine the importance of priority factors of the services provided by gyms, to examine the relationship of each factor with overall satisfaction and dissatisfaction by applying the IPA model; as well as to determine satisfaction with the service according to sex, age, and gymnasium. A total of 219 users participated, 51.1% of whom were men and 48.9% women, with a mean age of 25.10 ± 7.32 years. The CECASDEP (Questionnaire of Evaluation of the Quality Perceived in Sports Services) was used to measure service quality, structured into five factors: sports facilities (10 items), sports spaces (10 items), changing rooms-sanitary facilities (12 items), program of activities (9 items) and trainer/instructor (8 items). The analysis revealed that the main aspects to be improved in the gyms evaluated were sports facilities and changing rooms-sanitary facilities. Significant differences were recorded according to sex, age and type of gymnasium (p < 0.05). Finally, the IPA model indicated that, from the user's point of view, there is room for improvement and that efforts and resources should be focused on improving sports facilities and changing rooms-sanitary facilities, since these are the areas of greatest importance to users.